A Novel Authentication and Key Agreement Scheme for Countering MITM and Impersonation Attack in Medical Facilities - Maikol, Steve Olsen; Khan, Adnan Shahid; Javed, Yasir; Bunsu, Anderson Lau Anak; Petrus, Chelsten; George, Heindwick; Jau, Simon (International Journal of Integrated Engineering, 2020)
Authentication is used to enfold the privacy of the patient to implement security onto the communication between patients and service providers. Several types of research have proposed support for anonymity for contextual privacy in medical systems that are still vulnerable to impersonation attack and Man-in-the-middle attack. By using powerful technology that is used in medical facilities, it can help in building an advanced system. However, the same powerful tools can also be used by the attackers to gain personal profits and to cause chaos. The proposed countermeasure that is to be taken to prevent this kind of attacks is by implementing mutual authentication between users, their devices/mobile devices, and the system’s cloud server, and also a key agreement scheme together with the help of Elliptic Curve Cryptography (ECC). A novel authentication scheme which consists of two phases, a signature generation, and authentication process. The ECC implementation is to ensure that the keys are thoroughly secured and is not copy- able, together with a Key generation scheme that shields the system against impersonation attacks. The usage of Elliptic Curve Digital Signature Algorithm (ECDSA), in a signature generation, on the other hand, provides users more secure way to hide the user private key and bring additional security layer before proceeding to authentication phase due to the existence of extra elements of domain parameters. Authentication is still considered as a crucial component in maintaining the security of any critical facilities that require the CIA tried and non- repudiation as a need to maintain their data. It does not only apply to medical centers, but any organizations that possess valuable data that is needed to be protected also requires strong authentication protocols. Thus, the trend for the need of novel authentication protocols will keep on rising as technology gets fancier and fancier.